1987
DOI: 10.1093/carcin/8.7.967
|View full text |Cite
|
Sign up to set email alerts
|

Unique carcinogen enhancement of transformation phenotype displayed by cloned rat embryo fibroblast (CREF) cells treated with methyl methanesulfonate and infected with a specific hostrange mutant of type 5 adenovirus

Abstract: Pretreatment of cloned rat embryo fibroblast (CREF) cells with methyl methanesulfonate (MMS) prior to infection with wild-type 5 adenovirus (H5wt) or a temperature-sensitive mutant of Ad5 (H5ts125) results in an MMS dose-dependent enhancement of viral transformation. With both viral isolates, MMS enhanced the transformation frequency when normalized for cell toxicity but did not induce a carcinogen dose-dependent increase in the absolute number of foci above solvent-treated controls. In contrast, pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Abbreviations: MMS, methyl methanesuifonate; CREF, cloned rat embryo fibroblast; CET, carcinogen enhancement of transformation; Ad5, wild-type 5 adenovirus; H5hr1, host-range cold-sensitive mutant of Ad5; MOI, multiplicity of infection; PFU, plaque-forming unit; SSPE, 0 75 M NaCI, 50 m M NaH2P04, 5 rnM Na2EDTA, pH 7.4. viral DNA integration/expression or the cellular phenotype of transformants [7,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: MMS, methyl methanesuifonate; CREF, cloned rat embryo fibroblast; CET, carcinogen enhancement of transformation; Ad5, wild-type 5 adenovirus; H5hr1, host-range cold-sensitive mutant of Ad5; MOI, multiplicity of infection; PFU, plaque-forming unit; SSPE, 0 75 M NaCI, 50 m M NaH2P04, 5 rnM Na2EDTA, pH 7.4. viral DNA integration/expression or the cellular phenotype of transformants [7,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In order for DNA tumor viruses, such as W40, polyoma and adenovirus, to induce transformation of specific target cells, viral DNA must stably integrate into cellular DNA by a process presumed to involve illegitimate recombination [33,34]. The cellular-and virus-encoded proteins that mediate the integration event are not presently known, but the apparently random nature of viral DNA integration into cellular DNA argues against a specific cellular DNA sequence as a preferential site for viral DNA integration [ I 4,27,35-371. In previous studies we have demonstrated that MMS and y irradiation can enhance the frequency of viral transformation in CREF cells infected with the cold-sensitive host-range mutant of Ad5, H5hrl [6,12,14,161. The ability of these agents to increase viral transformation was shown to display strict temporal dependence and to require the synthesis of new cellular proteins I6.161.…”
Section: Discussionmentioning
confidence: 96%
“…genesis [6,[10][11][12]. In thisstudywe haveused CREF cells in combination with a specific host-range coldsensitive Ad5 mutant, H5hr1, and various antibiotic resistance genes and oncogenes to begin to address the potential relationship between the induction and repair of DNA damage and viral and oncogene-mediated transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All four of these viruses display the cs transformation phenotype of H5hrl [29,32,40]. Although similar in transformation phenotype to H5hr1, these viruses do not display the unique H5hrl-induced CET phenotype [7] (unpublished observations). An additional Ad5 mutant, H5d1105, which expresses a mutated 135 E l A-encoded 289-aa protein and the same gene products as the other mutants described above, is defective for transformation H2dll500, H5dl101, H5dl105, H5inl06, or H5d1520, the unique CET phenotype of H5Hrl was preserved ( Table 2).…”
Section: Suppression Of T H E Unique H5hrl Cet Phenotype By Wt Ad5mentioning
confidence: 92%